HUBUNGAN DEMOGRAFIS DENGAN MOTIF MEMBACA KORAN HARIAN NONSTOP PADA MASYARAKAT KELURAHAN SUKAHATI CIBINONG JAWA BARAT - fauziah fauziah fauziah (PRoMEDIA, 2016)
ABSTRACT This study aimed to determine the demographic relationship with reading motive Daily Nonstop newspaper to community village at Sukahati Cibinong West Java. This study uses a uses and gratification theory, demographic factors based on antecedent variables in the uses and gratification theory, and the theory of motive. This study uses a quantitative approach with survey method. Using simple random sampling. Based on the research results, the value of r (correlation coefficient) between the last education with a pattern reading a Daily Nonstop newspaper is equal to -0.761. In the table Guilford value of r (correlation coefficient) which is between 0.70 to 0.90 indicates a high or strong relationships and a negative sign indicates a negative relationship. Research conclusion that the relationship between education and the last is included in demographic variables have a high correlation or pattern reading a Daily Nonstop newspaper to community village  at Sukahati Cibinong, West Java is closely related to the last education of the respondents Keyword : Reading Motive, Newspaper, Community